The roles of public service motivation and humble leadership in promoting work engagement among healthcare professionals: 10.55131/jphd/2025/230108 - Hoang Nguyen, Kim (Journal of Public Health and Development, 2024)
Work engagement is the central issue for healthcare employees not only in preventing occupational stress but also in improving job performance. The purpose of this study is to examine if work engagement can be enhanced by public service motivation and humble leadership. The snowball sampling approach was used for building a healthcare professional sample of physicians and nurses. Instruments used in self-administered questionnaires were validated and commonly utilized in previous studies with appropriate reliability. The model fit indices (χ2 = 449.308; df = 227; χ2/df = 1.979; CFI = 0.935; TLI = 0.928; RMSEA = 0.063) and factor loadings (ranging from 0.64 to 0.86) indicated satisfactory reliability and validity of the constructs and their indicators. The findings demonstrated positive and significant path coefficients between public service motivation and work engagement (b = 0.218, p < 0.001). Humble leadership also exhibited a significantly positive relationship with work engagement (b = 0.231, p < 0.001). The findings further revealed that humble leadership served as a moderator to attenuate the relationship between public service motivation and work engagement (b = -0.140, p < 0.01). The positive nexus between public service motivation and work engagement was found to be stronger when healthcare supervisors demonstrated low levels of humble leadership. As such, this study advances the healthcare management literature by gaining insights into work engagement among healthcare professionals. An essential contribution to existing knowledge has been made by examining the relationships that exist between public service motivation, humble leadership, and work engagement. Based on the results, healthcare organizations should implement relevant policies in terms of recruitment and training to foster public service motivation and humble leadership in order to promote work engagement.